Personality and HbA1c: Findings from six samples. (October 2020) - Stephan, Yannick; Sutin, Angelina R.; Luchetti, Martina; Canada, Brice; Terracciano, Antonio
Highlights: Personality was related to haemoglobin A1c (HbA1c) in six samples of adults. Higher conscientiousness was related consistently to lower HbA1c level. BMI and physical activity mediated the link between conscientiousness and HbA1c. There were not consistent associations for the other four traits. Abstract: Personality traits are associated with risk of diabetes, but most research to date has relied on participants reported diagnosis rather than objective markers of glycaemia. The present study examined the association between the five major domains of personality (neuroticism, extraversion, openness, agreeableness and conscientiousness) and haemoglobin A1c (HbA1c). Participants (N > 26, 000) were individuals aged from 16 to 104 years from six large community samples from the US, Europe, and Japan who had data on personality, demographic factors, body mass index (BMI), physical activity, and HbA1c. Of the five factors, only higher conscientiousness was related consistently to lower HbA1c level across most samples and in the meta-analysis. Conscientiousness was also related to lower risk of HbA1c ≥6.5 % (OR = .85, 95 %CI = 0.80−0.90). BMI and physical activity partially mediated the link between conscientiousness and HbA1c. There were not consistent associations for the other four traits across the six samples and no consistent associations between personality and likelihood of undiagnosed diabetes. The present study found replicable associations between conscientiousness and HbA1c in adulthood. Assessment of conscientiousness may improve the identification of individuals at risk of diabetes and guide personalized interventions for regulation of HbA1c level.